2014
DOI: 10.1007/s40262-014-0163-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Roux-en-Y Gastric Bypass on the Pharmacokinetics of Oral Morphine Using a Population Approach

Abstract: RYGB and the BMI reduction that followed it dramatically increased the rate of morphine absorption and slightly increased morphine exposure. The dose of immediate-release forms of morphine may be divided in obese patients after RYGB to prevent adverse events due to early and high morphine plasma peaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 46 publications
0
49
1
Order By: Relevance
“…214 The researchers found that Roux-en-Y gastric bypass and subsequent weight loss radically increased the rate of morphine absorption and also somewhat increased morphine exposure. They suggested that the dose of immediate-release forms of morphine might be divided in obese patients after bypass to prevent adverse events due to early and high morphine plasma peaks.…”
Section: Interventional Pain Management In Obese Patientsmentioning
confidence: 99%
“…214 The researchers found that Roux-en-Y gastric bypass and subsequent weight loss radically increased the rate of morphine absorption and also somewhat increased morphine exposure. They suggested that the dose of immediate-release forms of morphine might be divided in obese patients after bypass to prevent adverse events due to early and high morphine plasma peaks.…”
Section: Interventional Pain Management In Obese Patientsmentioning
confidence: 99%
“…Sixteen from 60 phase 2 studies scored over 65% and were included for further analysis (Table 1) [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Pain had been measured and recorded in over 2000 subjects in randomized controlled trials (RCT, n=7) or observational studies (n=9).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, most studies have been performed on patients with Roux-en-Y gastric Bypass (RYGB). Many have demonstrated changes in drug absorption parameters that are certainly related to the smaller gastric pouch after surgery and the achlorydric state associated, and few showed change in overall exposure [3][4][5][6]. Thus, the consequences of restrictive procedures merit the same attention as time to maximal concentration (T max ) and maximal concentration (C max ) may change and have clinical consequences for some drugs.…”
Section: Weaknesses In the Research Done In This Fieldmentioning
confidence: 99%
“…An ideal pharmacological study would include pharmacokinetic analysis before and immediately after surgery, a few months later after the patient experienced weight loss, and ideally when the weight stabilized. We conducted a pharmacokinetic study in obese patients before, immediately after (8-15 days), and six months after surgery (OBEMO study) [4]. It was very difficult to conduct the study immediately after surgery.…”
Section: Potential and Challenges Of This Area Of Researchmentioning
confidence: 99%
See 1 more Smart Citation